3D-CALI: Automatic calibration for camera and LiDAR using 3D checkerboard. (15th November 2022) - Wang, Qing; Yan, Chao; Tan, Rongxuan; Feng, Youyang; Sun, Yang; Liu, Yu
Highlights: Automatic calibration of camera and LiDAR extrinsic parameters using a 3D checkerboard. Extract the complete plane quickly using seed point diffusion. Sorting the checkerboards and the corner points in the camera frame automatically. Abstract: Accurate and robust calibration of intrinsic and extrinsic parameters is crucial to multi-sensor simultaneous localization and mapping (SLAM) systems. However, extrinsic calibration of heterogeneous sensors is challenging owing to the differences in data acquisition methods. Therefore, we propose a more robust and convenient method to calibrate the intrinsic parameters for the camera and extrinsic parameters for cameras and light detection and ranging (LiDAR) sensors based on a 3D checkerboard. We tested the algorithm in simulation and real-world environments. Experiments in the simulation environment showed that our proposed method had similar accuracy as the state-of-the-art calibration method velo2cam_calibration. 1 However, our proposed algorithm had less interaction and was more automatic. The real-world test also confirmed the results of our proposed method. Thus, the proposed method is a convenient means to calibrate intrinsic parameters for cameras, and extrinsic parameters for cameras and LiDAR sensors based on a 3D checkerboard.